White ethnic New York: Jews, Catholics, and the shaping of postwar politics - Zeitz, Joshua M. (University of North Carolina Press, 2007)
1. Communities -- 2. Dissent -- 3. Authority -- 4. Fascism -- 5. Communism -- 6. Race -- 7. Reaction -- 8. Upheaval